Do reproduction and parenting influence personality traits? Insights from threespine stickleback - Stein, Laura R. (Anim Behav, 2016)
Although one of the hallmarks of personality traits is their consistency over time, we might expect personality traits to change during life history shifts. Becoming a parent is a major life history event, when individuals undergo dramatic behavioural and physiological changes. Here we employ a longitudinal experiment to ask whether personality changes in response to the experience of parenting in male threespine sticklebacks, Gasterosteus aculeatus. Life history theory predicts that males should be less risk averse after successfully parenting, and the neuroendocrinology of parenting suggests that parenting could reorganize the hormonal landscape and behaviour of fathers. We randomly assigned males to either an experimental group (reproduced and parented) or a control group (did not reproduce and parent), and repeatedly measured a personality trait (‘boldness’) and 11-ketotestosterone levels (11-kT, the major androgen in fishes) in individual males. In the control group, males became bolder over time. However, in the experimental group, boldness did not change. Furthermore, 11-kT changed dramatically in the experimental group, and changes in 11-kT in parents were associated with boldness after parenting ceased. Our study is one of the first to assess proximate and ultimate explanations for changes in personality as a function of reproduction and parenting.